Research of the Backfill Body Compaction Ratio Based on Upward Backfill Safety Mining of the Close-Distance Coal Seam Group - Xingping Lai; Leiming Zhang; Yun Zhang; Pengfei Shan; Peifeng Wan; Kaiwen Mu (Geofluids)
During upward backfill mining of the close-distance coal seam group, the reasonable design of the backfill body compaction ratio (BBCR) of lower coal seam goaf plays a key role in controlling overburden strata movement and deformation. In this paper, the feasibility discrimination method of upward caving mining was adopted; it was found that when the coal seam spacing was small, the recovery was not possible due to the instability of the upper coal strata equilibrium structure caused by the mining. Hence, the upward backfill mining method was proposed; combined with the migration control mechanism of backfill mining overburden strata, the dynamic evolution of crack propagation height of overburden strata during upward backfill mining was analyzed. Based on that, a layer spacing-BBCR-mining height (L-R-H) prediction model based on multiple linear regression analysis was established and the BBCR of close-distance coal seam group safe upward mining was determined combined with the engineering background. The results demonstrate that the main controlling factors of crack propagation in overburden strata during upward backfill mining were BBCR and mining height; the crack propagation height in overburden strata caused by mining decreased exponentially with the increase of BBCR and increased with the increase of mining height linearly. The lower coal seam engineering safety BBCR of upward backfill mining in the Dafosi Coal Mine was 87.2%, and the close-distance coal seam group safe upward mining was realized.